Designing and optimization of liposomal nano-carriers containing Nepeta persica extract and study of its cytotoxicity on the breast cancer cell line (MCF-7) - Farzaneh Barakat; Fatemeh Aboee-Mehrizi; Bibi Fatemeh Haghiralsadat; Mahmood Dehghani Ashkezari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2019)
Introduction: Studies have shown that plant compounds have significant anticancer effects that if the challenges of using them are resolved, Can be the successor to the synthetic compounds commonly used in cancer therapy. Therefore, in this study, the liposomal nano- carriers containing Nepeta persica extract have been investigated in order to improve the physicochemical characteristics and evaluation of its antitumor properties.